2012
DOI: 10.1159/000336544
|View full text |Cite
|
Sign up to set email alerts
|

Consent and Research Governance in Biobanks: Evidence from Focus Groups with Medical Researchers

Abstract: Much is known about patient attitudes to ethical and legal questions in the context of biobanking, particularly regarding privacy protection and consent. However, little is known about the attitudes of medical researchers who use biobanks for research to these issues. Four focus groups with medical researchers in the UK were conducted in 2010–2011. The study highlights a range of issues associated with the research oversight and consent process (including obtaining ethical approval to use biobank samples and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 64 publications
(40 reference statements)
0
44
0
2
Order By: Relevance
“…In a qualitative research project, Whitley et al 27 reported that scientists noted the difficulty in predicting the future research uses of biological samples and information. Similarly, a study examining genomic researchers' attitudes on informed consent found that the majority preferred a general or broad consent approach.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a qualitative research project, Whitley et al 27 reported that scientists noted the difficulty in predicting the future research uses of biological samples and information. Similarly, a study examining genomic researchers' attitudes on informed consent found that the majority preferred a general or broad consent approach.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were also found in a study where research ethics committees in the United Kingdom did not readily allow general consent forms permitting any future research and some committees distinguished DNA-related tests from other forms of research. 27 While it is interesting to see that exclusions are being incorporated into informed consent applications for biobanking, it remains to be seen whether they can be used to omit contentious research and sharing.…”
Section: (Participant 5)mentioning
confidence: 99%
See 1 more Smart Citation
“…El proyecto EnCoRe utiliza una plataforma web que permite a los participantes de investigación tener una relación interactiva con los gestores del biobanco y con la comunidad de investigación 32 . Desde la plataforma web se promueve un proceso dinámico, que hace hincapié en el re-contacto continuo con los donantes del biobanco, ofreciendo a ellos información "en tiempo real" de los proyectos específicos de investigación, lo cual permite a los participantes la opción de proporcionar o revocar fácilmente su consentimiento 33 . Bajo esta metodología interactiva, utilizado herramientas de informática, el CD propone ser un modelo de continua comunicación bidireccional entre los participantes en la investigación (donantes), y los investigadores, superando así el problema ético que implica la participación pasiva, propia del consentimiento amplio 34 .…”
Section: Consentimiento Informado Dinámicounclassified
“…Es factible que al no cumplirse las expectativas de los donantes, ellos puedan asumirlo como una falta o abuso de confianza y el reclutamiento menor sería la consecuencia, por lo tanto el costo/ beneficio de un mayor contacto debe ser sopesado de manera cuidadosa 38 . El poder proveer a los donantes de los biobancos de herramientas que les permitan un mayor control y tal vez nuevos derechos sobre su contribución, es probablemente el argumento más fuerte para un modelo de consentimiento dinámico e interactivo.…”
Section: Consentimiento Informado Dinámicounclassified